2018
DOI: 10.1002/jcla.22708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of human papillomavirus genotypes among women with high‐grade squamous intraepithelial lesion and invasive cervical cancer in Ganzhou, China

Abstract: Background Human papillomavirus (HPV) infection can lead to the development of cervical cancer. This study assessed the genotype distribution of HPV of high‐grade squamous intraepithelial lesion (HSIL) and invasive cervical cancer (ICC) in Ganzhou population. Methods A total of 935 females who got HPV testing from January 2016 to July 2018 in the maternal and child health hospital of Ganzhou were enrolled in the study, including 806 HSIL and 129 ICC. HPV detection and genotyping were tested by HPV Geno‐Array t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
6
5
1
Order By: Relevance
“…In general, there are substantial differences between different countries and geographical areas in genotype distribution of HPV infections 12. As in our study, several studies have shown that types 52 and 58 are the most commonly seen high-risk HPV types in patients without any intra-epithelial lesions 3–5 10 13.…”
Section: Discussionsupporting
confidence: 62%
“…In general, there are substantial differences between different countries and geographical areas in genotype distribution of HPV infections 12. As in our study, several studies have shown that types 52 and 58 are the most commonly seen high-risk HPV types in patients without any intra-epithelial lesions 3–5 10 13.…”
Section: Discussionsupporting
confidence: 62%
“…The most common types of HPV detected in women with one or more HPV infections were HPV 16 (consistently detected in all of our patients), 18 (83%), 258 45 (33%), 33 (31%), 59 (28%), 35 (12%), 31 (11%), 58 (8%), 39 and 73 (4%), 44, 54 and 68 (3%) and the rest less than 1%. The high prevalence of HPV16 and HPV18 reported in our study was expected, as these types are the two most common types of HPV worldwide [23][24][25][26]. Several studies [27][28][29] have shown that genotypes 16 and 18 are responsible for 70.7% of cervical cancers, which explains why they were chosen as target for HPV vaccines.…”
Section: Year Of Diagnosis Place Of Residencesupporting
confidence: 62%
“…According to the previously reported data, over 70% of women have had an HPV infection at least once in their lifetime, with about 10% having a lifelong persistent infection (Liao et al, 2018). Persistent HPV infection can cause abnormal proliferation of cells, and the accumulations of genetic damage leading to cancer of the cervix, vulva, vagina, anus, penis, and/or oropharynx (Crosbie et al, 2013;Hong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%